Moments of order statistics from nonidentically Distributed Lomax, exponential Lomax and exponential Pareto Variables (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, the probability density function and the cumulative distribution function of the rth order statistic arising from independent nonidentically distributed (INID) Lomax, exponential Lomax and exponential Pareto variables are presented. The moments of order statistics from INID Lomax, exponential lomax and exponential Pareto were derived using the technique established by Barakat and Abdelkader. Also, numerical examples are given.